PENGARUH PEMBELAJARAN IPA MENGGUNAKAN MODEL PEMBELAJARAN QUANTUM LEARNING (QL) BERBANTUAN MEDIA BUKU PINTAR TERHADAP KEMAMPUAN BERFIKIR KREATIF SISWA KELAS IV SD 107 SELUMA - Harmika, Lita; Widi Winarni, Endang; Muktadir, Abdul (UNIB Press, 2025)
The purpose of this study was to analyze the effect of Science Learning using the Quantum Learning (QL) learning model assisted by Smart Book media on students' creative thinking abilities. The type of data used is quantitative data using instruments in the form of interviews, documentation, question instruments, and expert validation sheets. Based on the results of the study, it was found that the use of Smart Book media in science learning had a significant effect on the dimensions of fluent thinking ability. This is indicated by the average posttest of fluent thinking ability in the control class of 71. Meanwhile, the average posttest result of the experimental class was 88. The use of Smart Book media in science learning has a significant effect on the dimension of flexible thinking ability. This is indicated by the average posttest of flexible thinking ability in the control class of 69. Meanwhile, the average posttest result of the experimental class was 90. The use of Smart Book media in science learning has a significant effect on the dimension of Original thinking ability. This is indicated by the average posttest of Original thinking ability in the control class of 67. Meanwhile, the average posttest result of the experimental class was 87. Furthermore, there is no relationship between the dimensions of fluent, flexible and Original thinking ability with the use of Smart Book media in science learning.